Development and application of mechanized maize harvesters - Li, Yang; Tao, Cui; Zhe, Qu; Kehong, Li; Xiaowei, Yin; Dandan, Han; Bingxin, Yan; Dongyue, Zhao; Dongxing, Zhang (International Journal of Agricultural and Biological Engineering, 2016)
Maize harvesting is one of the most important filed operations of maize production. As the accelerating development of maize industry, mechanized maize harvesting is widely accepted and used by farmers in the world. According to the harvesting methods, maize harvesters could be classified into two types, one is maize-for-grain harvesters, including pickers and grain harvesters, the other is whole plant harvesters, including forage harvesters and combined grain-stover harvesters. Structure characteristics, appropriate areas and relative technologies of those harvesters are described in this paper, i.e., pickers are suitable for multi-crop areas, Grain harvesters are mainly for one-crop areas when grain moisture content is lower than 25%, combined grain-stover harvesters are applicable in agro-pastoral ecotone, and forage harvesters are capable in large-scaled animal husbandry farming areas where large amount of silage are required. Meanwhile, the future development trend of the different harvesters is predicted. Big horsepower engines, enhanced working efficiency, automation and intelligence are required by large scaled farms. As maize breeding development, more varieties that are suitable for grain harvesting are put into practice, so grain combine harvesters will be popular in future.Keywords: maize, harvesting, picker, grain harvester, forage harvester, development trendDOI: 10.3965/j.ijabe.20160903.2380Citation: Yang L, Cui T, Qu Z, Li K H, Yin X W, Han D D, et al. Development and application of mechanized maize harvesters. Int J Agric & Biol Eng, 2016; 9(3): 15－28.